2011
DOI: 10.1111/j.1365-2923.2010.03896.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of clinical context in residents’ physical examination diagnostic accuracy

Abstract: Clinical context is associated with enhanced diagnostic accuracy of common valvular lesions. However, this effect seems linked to heuristic hypothesis generation and may predispose to premature diagnostic closure, anchoring and confirmation bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
(98 reference statements)
1
27
2
2
Order By: Relevance
“…No attempt was made to sequester residents as the purpose of the exam was entirely formative. Based on prior study with a comparable cohort of residents,12 we calculated a minimum sample size of 156 to detect a 20% difference in diagnostic accuracy assuming a power of 80% and α of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No attempt was made to sequester residents as the purpose of the exam was entirely formative. Based on prior study with a comparable cohort of residents,12 we calculated a minimum sample size of 156 to detect a 20% difference in diagnostic accuracy assuming a power of 80% and α of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that there are several hundred potential cardiac physical diagnostic findings 11. Yet clinicians report using only three to five findings for most cardiac diagnoses 12 13. Do clinicians collect enough information to pick the most useful three to five findings?…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, most diagnoses are attained through clinical assessment. (24,25) Only 4.8%-7.5% of diagnoses are attained through further laboratory testing. (24,26) Clinical skills, which include history-taking and physical examination, were once the primary means by which diagnosis and clinical monitoring were done.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies on cardiac diagnosis using a high‐fidelity simulator have identified that trainees rely excessively on the information provided from a short clinical stem. In these studies, participants were unable to overcome either a biased stem or their own initially misguided impression when performing a cardiac physical examination. These experiments suggest that trainees were unable to rely on cues from their physical examination and instead overvalued less predictive cues from clinical history in forming their diagnostic impressions.…”
Section: Application Of Cue Diagnosticity and Cue Utilisation In Medimentioning
confidence: 99%